Mineralogia e matéria orgânica de terra preta arqueológica e solos adjacentes não antrópicos na região do Apuí Amazonas - Santos, Luís Antônio Coutrim dos (2018)
The Brazilian Amazon presents in most of its extension, highly weathered, acid and low fertility natural soils. However, from the years of 1870 and 1871, the first reports about the Amazonian anthropic soils, known as Archaeological Dark Earth (ADE), of high natural fertility, high levels of phosphorus and organic carbon began to appear, as well as the presence of artifacts lithic and ceramic. Mulatto Earth (ME) are anthropic soils that generally occur over a wide range surrounding ADE soils. These soils have their training related to long-term indigenous crops. The ADE are one of the most studied anthropic soils in the world, with great scientific efforts to reproduce the types of organic compounds observed in these soils. In the present work the following hypotheses were investigated: Soil organic matter (SOM) of ADEs and MEs present different levels and similar stabilities; Formation of iron oxides of low crystallinity occurs due to the great increase of organic material over time, during the formation of ADEs; It is possible to distinguish anthropic soils from non-anthropic soils by their chemical, mineralogical and organic matter. The objective of the present work is to evaluate the mineralogy and to characterize the chemical composition of the humin fraction in ADE, ME and non - anthropogenic soils in Apuí, Amazonas. The study areas are located in the southern mesoregion of the state of Amazonas, more precisely in the municipality of Apuí. The work was done evaluating anthropic soils ADE and ME and non-anthropic soils (NAS), in a total of six soil profiles. Morphological, physical and chemical analyzes were carried out to characterize the soils. For the study of mineralogy, X-ray diffraction and Fourier transform Infrared (FTIR) were used, as well as the magnetic susceptibility of the soils. The humin fraction (HumF) of SOM was separated, purified with 10% hydrofluoric acid, characterized by FTIR. The soil moisture content of ME presented similar composition to ADE soil, however, presented a lower degree of aromaticity. The mineralogical assemblage of the soils of ADE, ME and NAS are similar, however, gibbsite was only found in ADE and ME soil, whereas maghemite reflections were more expressive in ADE and ME soil than in NAS. Also, a difference of goethite crystallinity is observed, where it presents greater crystallinity in the NAS in comparison to the anthropic soils. The ADE soils present calcium enrichment calculated by the mass transport function for all horizons, thus showing that the anthropic influence goes beyond the horizons A, and even alter the subsurface horizons.